GAMBARAN PERILAKU PEMANFAATAN LOLOH CEMCEM SEBAGAI OBAT HERBAL DI DESA PENGLIPURAN - Ni Putu Ayu Meilla Kartika Putri; Ni Putu Aryati Suryaningsih; Gde Palguna Reganata (JOURNAL SCIENTIFIC OF MANDALIKA (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2023)
The world of health is starting to realize that there are hidden dangers behind the excessive use of synthetic drugs, so people's attention is now turning to hereditary medicine. One of them is the use of traditional herbal lolo cemcem. Preliminary studies found that 9 out of 10 residents of Penglipuran Village prefer loloh cemcem as herbal medicine because it has many benefits for treatment. The purpose of this study was to determine the behavior of using loloh cemcem as an herbal medicine in the Penglipuran village community. The research method used is a qualitative approach with an ethnographic study design and data collection techniques by means of interviews. The results showed that loloh cemcem had been used for generations, the community knew the benefits of loloh cemcem, and the personal experience felt by the community regarding the use of loloh cemcem, had the same processing method, and there were differences in how to use it in the dosage section and how many times a day to drink it , and the utilization of lolo cemcem is supported from a family perspective. Based on the research findings, knowledge about loloh cemcem has been passed down from generation to generation and the public has the view that loloh cemcem is not just a traditional refreshing drink but can be used as herbal medicine. The benefits of loloh cemcem are believed by the people of Penglipuran Village in medicine and health, namely to overcome constipation (difficulty defecating), heartburn, bleeding gums and can increase appetite.